How much is clean air worth? : calculating the benefits of pollution control - Rabl, Ari; Spadaro, Joseph V.; Holland, Mike; Cambridge eBooks (Cambridge : Cambridge University Press, 2014)
How Much is Clean Air Worth? offers readers a comprehensive overview of the core methodologies and tools used to quantify the impacts and damage costs of pollution. The book begins by reviewing the tools used for environmental assessments and shows that a rational approach requires an impact pathway analysis (IPA) for each of the possible impacts of a pollutant, i.e. an analysis of the chain emission -> dispersion -> exposure-response functions -> monetary valuation. The IPA methodology is explained in full and illustrated with worked examples, and difficulties are discussed and uncertainties analysed. In addition to detailed computer models, a very simple model (the 'Uniform World Model') is presented, enabling readers to make estimates for cases where no results are available. Published results for electricity, waste treatment and transport are reviewed, with a thorough discussion of policy implications. This book will appeal to a broad mix of academics, graduate students and practitioners in government and industry working on cost-benefit analysis, environmental impact analysis and environmental policy.
Introduction -- Tools for environmental impact and damage -- Exposure-response functions for health impacts -- Impacts for air pollution on building materials -- Agriculture, forests, and ecosystems -- Other impacts -- Atmospheric dispersion of pollutants -- Multimedia pathways -- Monetary valuation -- The costs of climate change -- Uncertainty of damage costs -- Key assumptions and results for cost per kg of pollutant -- Results for power plants -- Results for waste treatment -- Results for transport -- Lessons for policy makers.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Air -- Pollution -- Economic aspects; Air quality management -- Economic aspects; Air -- Pollution -- Measurement; Electronic books